Comprehension of direct extraction of hydrophilic antioxidants using vegetable oils by polar paradox theory and small angle X-ray scattering analysis. (15th April 2015) - Li, Ying; Fabiano-Tixier, Anne Sylvie; Ruiz, Karine; Rossignol Castera, Anne; Bauduin, Pierre; Diat, Olivier; Chemat, Farid
Highlights: Polar paradox theory inspired a new way for oil enrichments in hydrophilic antioxidants. SAXS was firstly used in comprehension of dissolving mechanism. A truly green extraction process has been developed in a biorefinery way. Abstract: Since the polar paradox theory rationalised the fact that polar antioxidants are more effective in nonpolar media, extractions of phenolic compounds in vegetable oils were inspired and achieved in this study for obtaining oils enriched in phenolic compounds. Moreover, the influence of surfactants on the extractability of phenolic compounds was experimentally studied first, followed by the small angle X-ray scattering analysis for the oil structural observation before and after extraction so as to better understand the dissolving mechanism underpinning the extraction. The results showed a significant difference on the extraction yield of phenolic compounds among oils, which was mainly dependent on their composition instead of the unsaturation of fatty acids. Appropriate surfactant additions could significantly improve extraction yield for refined sunflower oils, which 1% w/w addition of glyceryl oleate was determined as the optimal. Besides, 5% w/w addition of lecithin performed the best in oil enrichments compared with mono- and di-glycerides.